Do Preschool Teachers’ Beliefs About Age-related Emotional Development Impact Preschoolers’ Emotion Understanding? - Дарья А. Бухаленкова; Маргарита С. Асланова; Злата В. Айрапетян; Маргарита Н. Гаврилова (Rossijskij psihologičeskij žurnal., 2021)
Introduction. Beliefs of preschool teachers about specific characteristics of children’s emotional development have been studied mainly in the context of the used methods for teaching children. However, the relationship with the development of emotion understanding in preschoolers remains underexplored. Children’s emotion understanding includes such components as recognizing emotions, understanding the effect of external causes, the role of desires, beliefs, memories, and moral rules in the formation of emotions, and understanding that emotions may be hidden and mixed and that they may be regulated. This study aims to identify the influence that teachers’ beliefs about the development of certain components of children’s emotion understanding exerts on the actual level of emotion understanding in 5–6-year-olds. Methods. The study involved 16 senior kindergarten groups; in total 16 preschool teachers we interviewed, and 324 children were assessed. To identify teachers’ beliefs about children’s emotion understanding, we used the method of structured interview. Children’s emotion understanding was assessed using the Test of Emotion Comprehension. Results. Preschool teachers were quite accurate in their estimation of the age when children master the majority of components of emotion understanding (except for understanding the role of beliefs, the role of moral rules in the formation of emotions, and mixed emotions). At the same time, in groups where teachers believed that understanding of these aspects was not yet available to children, preschoolers coped with the tasks testing these abilities more successfully than children in groups where teachers believed that these skills had already been formed. Discussion. We can assume that preschool teachers who believed that children in their groups had not yet mastered these skills were more focused on teaching children these components of emotion understanding.